Gymnaster koraiensis and its major components, 3,5-di-O-caffeoylquinic acid and gymnasterkoreayne B, reduce oxidative damage induced by tert-butyl hydroperoxide or acetaminophen in HepG2 cells - Jho, Eun Hye; Kang, Kyungsu; Oidovsambuu, Sarangerel; Lee, Eun Ha; Jung, Sang Hoon; Shin, Il-Shik; Nho, Chu Won (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2013)
We investigated the protective effects of Gymnaster koraiensis against oxidative stress-induced hepatic cell damage. We used two different cytotoxicity models, i.e., the administration of tert-butyl hydroperoxide (t-BHP) and acetaminophen, in HepG2 cells to evaluate the protective effects of G. koraiensis. The ethyl acetate (EA) fraction of G. koraiensis and its major compound, 3,5-di-O-caffeoylquinic acid (DCQA), exerted protective effects in the t-BHP-induced liver cytotoxicity model. The EA fraction and DCQA ameliorated t-BHP-induced reductions in GSH levels and exhibited free radical scavenging activity. The EA fraction and DCQA also significantly reduced t-BHP-induced DNA damage in HepG2 cells. Furthermore, the hexane fraction of G. koraiensis and its major compound, gymnasterkoreayne B (GKB), exerted strong hepatoprotection in the acetaminophen-induced cytotoxicity model. CYP 3A4 enzyme activity was strongly inhibited by the extract, hexane fraction, and GKB. The hexane fraction and GKB ameliorated acetaminophen-induced reductions in GSH levels and protected against cell death.
Keywords: SINGLE-STRAND BREAKAGE; BENZOQUINONE IMINE; HUMAN HEPATOCYTES; BUTYLHYDROPEROXIDE; HEPATOTOXICITY; MECHANISMS; TOXICITY; OXIDANTS; DISEASES; STRESS